Friction-condition-dependent sulfide and sulfate evolution on dialkylpentasulfide tribofilm studied by XANES - Ganlin Zheng; Tongmei Ding; Songhong Pang; Lei Zheng; Tianhui Ren (Friction)
Abstract The effects of friction conditions, such as rotational speed, frictional time, and applied load, on the evolution mechanism of sulfide and sulfate on the top and bottom layers of tribofilm were investigated by total electron yield (TEY) and fluorescence yield (FY) mode X-ray absorption near-edge structure (XANES) spectra in the same beam line (4B7A). The results demonstrated that the top and bottom layers of tribofilms were covered by sulfide and sulfate. The addition of dialkylpentasulfide (DPS) could form complex nonuniform tribofilm. In addition, the friction condition (speed, load, or time) has its unique role in the generation of sulfide and sulfate at a specific depth on the tribofilm surface. The enhancement of friction conditions could promote the sulfur tribochemical reaction in a comparatively large range and alter the relative intensity of sulfurization and the sulfur-oxidizing process.